Investigations on Physical and Chemical Characteristics of Some Pomegranate Genotypes (Punica granatum L.) of Tokat Province in Turkey - Ozkan, Yakup (Asian Journal of Chemistry, 2016)
The physical and chemical analyses of five different pomegranate genotypes (Punica granatum L.) were investigated for two years. The average fruit weight lies between 140.9-281.1 g, skin bottom colour is yellow in all types, skin upper colour pink-red, skin thickness 2.82-3.59 mm, fruitlet colour clear pink-dark red, the weight of 100 kernels 24.1-41.4 g and the percentage of kernels ranged between 43.4-61.3%. In addition, the total soluble solid content was found between 13.5-16.7%, while total acid varied between 2.66-3.58%.